When Can Acute Supraglottitis Patients Be Discharged from Intensive Care?. (23rd August 2013) - Shaul, Chanan; Israel, Ariel; Schwarz, Yehuda; Peleg, Uri; Sichel, Jean‐Yves
Abstract : Objectives: Acute supraglottitis in adults is usually managed by admitting the patient for airway monitoring in the intensive care unit (ICU). However, data are lacking on when patients could be transferred from the ICU to the ward. Our aim is to suggest decision criteria for transferring patients to the regular ward. Methods: A retrospective review of medical records from adult patients admitted for supraglottitis to our center was conducted. The information obtained included airway management, length of stay in the ICU and in the ward, clinical condition of the patients at the time of their transfer from the ICU to the ward, and outcome. Results: Between 2006 and 2012, 38 adult patients were treated in our department for supraglottitis with antibiotics and systemic steroids. All patients were admitted to the ICU for monitoring. Fiberoptic laryngoscopy was performed every 12 hours. 5 patients required intubation at admission. 33 patients were admitted to the ICU for monitoring and did not require further intubation. Average time in the ICU was 27.4 hours. We observed that all patients who had a mild swelling regression did not deteriorate or require re‐intubation or re‐admission to the ICU. They were all discharged from the regular ward without any complications. Conclusions: Patients without severe airway compromise could undergo monitoring in the ICU without intubation. Since all patients who began to improve did not suffer from deterioration afterwards, we suggest that even mild airway improvement could be considered as a sufficient criterion for safe transfer of patients to the regular ward.